Rancang Bangun Alat Pendeteksi Kualitas Udara Portable berbasis Internet of Things (IoT) - Miranto, Afit; Tsaqib Adnan, Fikar (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2023)
In everyday life, air in the atmosphere has various forms such as gas, air particles and so on. One of them that is often inhaled by humans is oxygen. However, various kinds of air particles can have a negative impact on health, namely respiratory tract infections if inhaled or exposed to a predetermined reasonable threshold period. Therefore, it is necessary to prevent a tool to determine the level of air quality and its status and the location point that is compact in size and easy to carry. The system that is built has air pollution detection parameters including particulate matter, carbon monoxide gas and nitrogen dioxide. In the tool there is a system equipped with technology, namely monitoring by connecting to the cloud server in real time. Where, these data show the value that has been processed into the Air Pollution Standard Index (ISPU) and the data can be read back without worrying. On the surface of the tool displays the status of the carbon monoxide parameter air quality, for other parameter data can be seen in the cloud server database. Additional features contained in this system are being able to find out the location of the device that has been installed and the percentage value of the available battery capacity. After testing the tool, the error value on sensor readings for each CO, NO2, PM2.5, temperature, humidity, pressure gas is 2.26%, 11.318%, 4.567%, 4.138%, 17.17%, 0.036%. Keywords: Air Quality, CO, IoT, ISPU, NO2, PM2.5, Sensor.